Mediating role of intrinsic motivation in relationship between perception of organizational justice and extra-role behaviors among Wasit University faculty members - Abdulridha Hussein Shihmani, Hayder; Manshaee, Gholamreza; Marid Jabur, Adnan; Mahdad, Ali (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aims to analyze the mediating role of intrinsic job motivation in relationship between perception of organizational justice and extra-role behaviors of faculty members of Wasit University in Iraq.Methodology: Research method was Correlation and statistical population included all faculty members of Wasit University in the spring and summer of 1403 (summer of 2024). 250 people were selected from mentioned statistical population through convenience sampling method, and answered to three questionnaires of extra-role behaviors (Lee and Allen, 2002), perception of organizational justice (Colquitt, 2001), and internal job motivation (Gagne et al. 2015). Research data were analyzed using Pearson's correlation coefficient and Structural Equation Modeling (SEM) by using SPSS version 26 and AMOS version 25.Findings: The results showed that the perception of organizational justice has a significant relationship with internal job motivation and extra-role behaviors (p